INDUKSI KALUS EMBRIOGENIK DARI EKSPLAN TUNAS APIKAL TANAMAN JARAK PAGAR (Jatropha curcas L.) DENGAN PENGGUNAAN 2,4 D DAN TDZ - Lizawati . (Bioplantae, 2012)
This studyaims at determine the interactionbetween the different level of 2.4-D andTDZ concentrations, to induction theembryogeniccallus of physic nut. This Research used completely randomized design with factorial treatment pattern, which consists oftwofactors :concentration of2,4 –D, which consists of 5levels : 0.0, 2.5,  5.0,  7.5, 10.0 ppm, and the concentration ofTDZconsists of 5levels: 0.0,  0.5,  1.0, 1.5, 2.0 ppm. The results showes that there are interactions between 2,4-D andTDZ to  formingcallus   ofthe apicalbudexplants of physic nut.The combination of5.0 ppm2,4-D + 1.0ppmTDZand7.5ppm2,4-D + 1.5ppmTDZproducedthe time appearing of callusfastestcompared toother  treatments. The highestpercentage ofcallus formation occuredin thetreatment of2.5ppm2,4-D + 1.0ppmTDZand7.5ppm2,4-D + 1.5ppmTDZ. Whiteyellow color, shinyand friable are characteristicof embryogenic callusproduced on thetreatment of0.0 ppmand 2.5ppm2,4-D with the addition ofTDZata concentration of 0.5ppm, 1.0 ppm, 1.5 ppmand 2.0ppm.   Key words : embryogenic, callus, TDZ